2022
DOI: 10.3171/2022.8.focus22239
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant stereotactic radiosurgery with or without postoperative fractionated radiation therapy in adults with skull base chordomas: a systematic review

Abstract: OBJECTIVE The objective of this retrospective study was to compare the survival of patients with biopsy-proven skull base chordoma who had undergone stereotactic radiosurgery (SRS) with versus without prior fractionated radiation therapy (RT). METHODS Relevant articles from database inception to September 2021 were retrieved from the PubMed, Scopus, Web of Science, and Cochrane databases for a systematic review of treatment protocols. Studies were included if they 1) involved adult patients (age ≥ 18 years) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…Considering this significant recurrence rate also in elderlies, we can suggest that postoperative radiation therapy should be advised also in this population to prevent early progression and increase their overall survival. [24][25][26] It has been reported that radiotherapy could increase the risk of delayed CSF leak in patients already operated trough an EEA, therefore we used to fill the surgical field with abdominal fat, covered with mucoperiosteum even whether no intra-operative leak is observed. [24][25][26] This maneuver could also be particularly useful in elderlies, which could be more severely affected by the development of delayed leak with meningitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering this significant recurrence rate also in elderlies, we can suggest that postoperative radiation therapy should be advised also in this population to prevent early progression and increase their overall survival. [24][25][26] It has been reported that radiotherapy could increase the risk of delayed CSF leak in patients already operated trough an EEA, therefore we used to fill the surgical field with abdominal fat, covered with mucoperiosteum even whether no intra-operative leak is observed. [24][25][26] This maneuver could also be particularly useful in elderlies, which could be more severely affected by the development of delayed leak with meningitis.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26] It has been reported that radiotherapy could increase the risk of delayed CSF leak in patients already operated trough an EEA, therefore we used to fill the surgical field with abdominal fat, covered with mucoperiosteum even whether no intra-operative leak is observed. [24][25][26] This maneuver could also be particularly useful in elderlies, which could be more severely affected by the development of delayed leak with meningitis.…”
Section: Discussionmentioning
confidence: 99%
“…26,28 Similarly, in a metaanalysis, Di Maio et al 29 did not detect any statistically significant difference in tumor control rates between various radiation treatment modalities. Similarly, in a meta-analysis of SRS for primary and recurrent skull base chordomas, comparing SRS with or without prior FRT, Bin-Alamer et al 30 did not detect any difference in neither overall survival nor tumor control between the 2 groups. Our results propose that adjuvant postoperative SRS alone is a potential alternative to conventional postresection FRT modalities and may reduce unnecessary risk related to additional radiation and need for additional treatment.…”
Section: Tumor Controlmentioning
confidence: 91%
“…The median tumor volume was nonsignificantly higher in the SRS group (6.0 cc [IQR, 3.3-12.1]) compared with the FRT+SRS group (3.0 cc [IQR, 1.6-8.6]; P = .06), whereas the median prescription volume was significantly higher in the SRS group (6.6 cc [IQR, 3.3-15.2]) compared with the FRT+SRS group (3 cc [IQR, 1.6-8.6]; P = .03; Table 2). The SRS group had a significantly higher median marginal dose (18 Gy [IQR, [16][17][18]) compared with the FRT+SRS group (16 Gy [IQR, [13][14][15][16][17][18]; P = .01) and a significantly higher median maximum dose (36 Gy [IQR, 32-40]) compared with the FRT+SRS group (32 Gy [IQR, [27][28][29][30][31][32][33][34][35][36]; P = .01), and both groups had a similar median isodose line (50%).…”
Section: Cohort Demographics and Characteristicsmentioning
confidence: 99%
“…Several excellent reviews of the literature for proton therapy in skull base chordomas have been published recently including systematic reviews. [42][43][44][45][46] Other significant series are summarised in Table 1. 15,37,[47][48][49] To date, there have been no randomised studies comparing proton therapy and photon therapy.…”
Section: Review Of Evidence Regarding Use Of Radiotherapymentioning
confidence: 99%